Improvements in the Production of Aspergillus Oryzae β-galactosidase Crosslinked Aggregates and Their Use in Repeated-Batch Synthesis of Lactulose - Vera-Vera, C (Elsevier B.V., 2020)
Aspergillus oryzae β-galactosidase was immobilized by aggregation and crosslinking, obtaining catalysts (CLAGs) well-endowed for lactulose synthesis. Type and concentration of the precipitating agent were determinants of immobilization yield, specific activity and thermal stability. CLAGs with specific activities of 64,007, 48,374 and 44,560 IUH g−1 were obtained using 50% v/v methanol, ethanol and propanol as precipitating agents respectively, with immobilization yields over 90%. Lactulose synthesis was conducted at 50 °C, pH 4.5, 50% w/w total sugars, 200 IUH g−1 of enzyme and fructose/lactose molar ratio of 8 in batch and repeated-batch operation. Lactulose yields were 0.19 g g−1 and 0.24 g g−1 for fructose to lactose molar ratios of 4 mol mol−1 and 8 mol mol−1 while selectivities were 3.3 mol mol−1 and 6.6 mol mol−1 respectively for CLAGs obtained by ethanol and propanol precipitation. Based on these results, both CLAGs were selected for the synthesis in repeated-batch mode. The cumulative mass of lactulose in repeated-batch was higher with CLAGs produced by ethanol and propanol precipitation than with the free enzyme. 86 and 93 repeated-batches could have been respectively performed with those CLAGs considering a catalyst replacement criterion of 50% of residual activity, as determined by simulation. © 2019 Elsevier B.V.